Law relating to computer crimes and a commentary on the Computer Crimes Act no. 24 of 2007 - Indatissa, Kalinga (Colombo : Kalinga Indatissa, 2008)
With reference to Sri Lanka.
Includes bibliographical references.
Keywords: Computer crimes -- Law and legislation -- Sri Lanka